The Oxford illustrated history of the world - Fernandez-Armesto, Felipe (Oxford, UK Oxford University Press, 2019)
Imagine the planet, as if from an immense distance of time and space, as a galactic observer might see it--with the kind of objectivity that we, who are enmeshed in our history, can't attain. The Oxford Illustrated History of the World encompasses the whole span of human history. It brings together some of the world's leading historians, under the expert guidance of Felipe Fernandez-Armesto, to tell the 200,000-year story of our world, from the emergence of homo sapiens through to the twenty-first century: the environmental convulsions; the interplay of ideas (good and bad); the cultural phases and exchanges; the collisions and collaborations in politics; the successions of states and empires; the unlocking of energy; the evolutions of economies; the contacts, conflicts, and contagions that have all contributed to making the world we now inhabit.
Part I. Children of the ice: the peopling of the world and the beginnings of cultural divergence, c.200,000 to c.12,000 years ago -- Humanity from the ice: the emergence and spread of an adaptive species -- The mind in the ice: art and thought before agriculture -- Part 2. Of mud and metal: divergent cultures from the emergence of agriculture to the 'crisis of the Bronze Age', c.10,000 BCE-c.1,000 BCE -- Into a warming world -- The farmers' empires: climax and crises in agrarian states and cities -- Part 3. The oscillations of empires: from the 'dark age' of the early first millennium BCE to the mid-fourteenth century CE -- Material life: Bronze Age crisis to the black death -- Intellectual traditions: philosophy, science, religion, and the arts, 500 BCE-1350 CE -- Growth: social and political organizations, 1000BCE-1350 CE -- Part 4. The climatic reversal: expansion and innovation amid plague and cold from the mid-fourteenth to the early nineteenth centuries CE -- A converging world: economic and ecological encounters, 1350-1815 -- Renaissances, reformations, and mental revolutions: intellect and arts in the early modern world -- Connected by emotions and experiences: monarchs, merchants, mercenaries, and migrants in the early modern world -- Part 5. The great acceleration: accelerating change in a warming world, c.1815-c.2008 -- The Anthropocene epoch: the background to two transformative centuries -- The modern world and its demons: ideology and after in arts, letters, and thought, 1815-2008 -- Politics and society in the kaleidoscope of change: relationships, institutions, and conflicts from the beginnings of western hegemony to American supremacy -- Epilogue.
Mr. Edwin Estrera (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Tertiary/Undergraduate, General.
Keywords: World history -- Pictorial works; Pictorial works